Quantifying restoration effectiveness using multi‐scale habitat models: implications for sage‐grouse in the Great Basin. Issue 3 (24th March 2014) - Arkle, Robert S.; Pilliod, David S.; Hanser, Steven E.; Brooks, Matthew L.; Chambers, Jeanne C.; Grace, James B.; Knutson, Kevin C.; Pyke, David A.; Welty, Justin L.; Wirth, Troy A.
Abstract : A recurrent challenge in the conservation of wide‐ranging, imperiled species is understanding which habitats to protect and whether we are capable of restoring degraded landscapes. For Greater Sage‐grouse ( Centrocercus urophasianus ), a species of conservation concern in the western United States, we approached this problem by developing multi‐scale empirical models of occupancy in 211 randomly located plots within a 40 million ha portion of the species' range. We then used these models to predict sage‐grouse habitat quality at 826 plots associated with 101 post‐wildfire seeding projects implemented from 1990 to 2003. We also compared conditions at restoration sites to published habitat guidelines. Sage‐grouse occupancy was positively related to plot‐ and landscape‐level dwarf sagebrush ( Artemisia arbuscula, A. nova, A. tripartita ) and big sagebrush steppe prevalence, and negatively associated with non‐native plants and human development. The predicted probability of sage‐grouse occupancy at treated plots was low on average (0.09) and not substantially different from burned areas that had not been treated. Restoration sites with quality habitat tended to occur at higher elevation locations with low annual temperatures, high spring precipitation, and high plant diversity. Of 313 plots seeded after fire, none met all sagebrush guidelines for breeding habitats, but approximately 50% met understory guidelines, particularly for perennial grasses. This pattern was similar for summer habitat. Less than 2% of treated plots met winter habitat guidelines. Restoration actions did not increase the probability of burned areas meeting most guideline criteria. The probability of meeting guidelines was influenced by a latitudinal gradient, climate, and topography. Our results suggest that sage‐grouse are relatively unlikely to use many burned areas within 20 years of fire, regardless of treatment. Understory habitat conditions are more likely to be adequate than overstory conditions, but in most climates, establishing forbs and reducing cheatgrass dominance is unlikely. Reestablishing sagebrush cover will require more than 20 years using past restoration methods. Given current fire frequencies and restoration capabilities, protection of landscapes containing a mix of dwarf sagebrush and big sagebrush steppe, minimal human development, and low non‐native plant cover may provide the best opportunity for conservation of sage‐grouse habitats.